Solving crises in capitalism and democracy - Hage, Jerald, 1932- author. Link
1 online resource
Keywords: Democratic capitalism is beset with many problems producing rising inequality and growing authoritarianism. Examples include homelessness, food insecurity, child poverty, mass killings, and rising antisemitism. These problems encourage the election of authoritarian leaders. This book describes new strategies to promote inclusion and reduce inequality that do not require D.E.I. policies or affirmative action, reduce government spending without wholesale firings and in the process make government more effective, and reduce individual distrust while increasing people's willingness to donate time and money to important causes that help others and the world.The new strategies create systematic coordinated inter-organizational networks or SCIONs to achieve the following four objectives: Increase the amount and radicalness of product or service innovation Create a more diverse labor force with more and more varied skills Make health and welfare programs more efficient and effective Restore the balance between law and freedom in community safety As a new mode of coordination, SCIONs provide to platforms for continued dialogue among diverse viewpoints, decentralize problem solving, and stimulate considerable organizational adaptiveness. They overcome the limitations of market and state coordination.This macro sociological theory offers policy guidelines that might lead to future jobs for sociologists, provide tools to overcome managerial satisficing, and speed responses to change. A detailed case study is provided with a discussion of the feasibility of creating SCIONs and whether or not elites will resist this new coordination mode. Given the broad range of topics, this book is relevant for many courses in the social sciences, for those interested in policy and social change, as well as the general public.